EU Accession Countries' Specialisation Patterns in Foreign Trade and Domestic Production - What can we infer for catch-up prospects? - Johannes Stephan (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2003)
This paper supplements prior analysis on 'patterns and prospects' (Stephan, 2003) in which prospects for the speed of future productivity growth were assessed by looking at the specialisation patterns in domestic production. This analysis adds the foreign trade sphere to the results generated in the prior analysis. The refined results are broadly in line with the results from the original analysis, indicating the robustness of our methods applied in either analysis. The most prominent results pertain to Slovenia and the Slovak Republic. Those two countries appear to be best suited for swift productivity catch-up from the viewpoint of sectoral specialisation. Poland and Estonia exhibit the lowest potentials. Only for the case of Poland would results suggest bleak prospects.
urn:nbn:de:gbv:3:2-20879
Keywords: P; O; 330; manufacturing industry; foreign trade specialisation; structural change; productivity growth; productivity gap; transition economies; catch-up; Internationale Arbeitsteilung; Verarbeitendes Gewerbe; Produktivität; Entwicklungskonvergenz; Arbeitsteilung; Schätzung; EU-Erweiterung; Osteuropa